Familial Mesiodens: A study of 28 patients - Purcarea, Razvan; Severin, Emilia; Albu, Cristina-Crenguta; Albu, Dinu-Florin (International Journal of Medical Research and Review, 2015)
Introduction: The most commonly encountered tooth among the supernumeraries is the mesiodens. A genetic cause has often been revealed, suggested by the familial pattern. Objectives: To analyze the variability of this supernumerary tooth as shown in the clinical cases. We want to investigate the transmission pattern through family members. Methods: The study was based on 28 patients aged between 8 and 23 years. We delineated three groups of patients, according to the dimensions, position on the dental arch and shape of the mesiodens: 1). Conical, not alligned (erupted towards the palat); 2). Conical, well alligned and without occlusal interference. 3). Rudimentary shape supernummerary tooth. Radiographic and clinical examinations were used to establish the diagnosis. Family tree documentation has also been recorded. Results: The cases we analyzed were concerning both temporary and permanent dentition. Mesiodens was observed as unique numeric dental anomaly or associated with other mesiodens or even anodontia. Usually, unique mesiodens runs among family members. The clinical form of supernumerary manifestation is variable in different members and different generations, indicating various patterns of character transmission within families. Conclusions: Unique or multiple, the mesiodens is an extra tooth that interferes with normal temporary and permanent dentition. Although in a few cases it may appear as a de novo mutation, usually its presence is due to variable expressivity and locus heterogeneity within a family. Clinical diagnosis, family screening and genetic advice are recommended in order to prevent, anticipate and treat the complications produced by the presence of supernumerary teeth.